Análise de adesão e crescimento bacteriano em superfícies modelo: uma avaliação em ampla escala de comprimento - Sousa, Francisco de Assis (2017)
In the present work the adhesion and bacterial growth on silicon substrates (modified through anisotropic corrosion with KOH) were evaluated in a large scale of length (nanometer to millimeter) using a method based on computational processing of images. Firstly, the topographies of the Si surfaces obtained were characterized by a set of topographic parameters (Ra, Rq Rsk, Rk, ξ e D). Posteriorly, the large-field confocal optical microscopy (LF-CLSM) imaging was used to characterize the whole substrate (5  5 mm) after incubation of these in a bacterial suspension of Staphylococcus aureus. The computational analysis of these images allowed to quantitatively compare the occupation (in %-area), amount of bacteria and agglomerates, and their size distributions. The results showed that samples of low roughness (Rq ~32 nm) present lower amount of bacteria adhered, and less occupation of area for a 3 h incubation time. On the other hand, lower bacterial growth was observed for more rough sample (Rq ~330 nm) for the 5 h incubation time. In this sample, microestructures (large pyramids) were formed on its surface as a result of anisotropic corrosion with KOH. However, for times greater than 18 and 26 h it was evidenced that all surfaces under study were unable to prevent the formation of biofilms, resulting in average values of area occupation close to 100 %, evaluated over an area of 3,6  3,6 mm. Through algorithms developed to process stacks of the optical slices of these biofilms, it was possible to observe that there were no great differences in the biomass amounts of the same ones. The methods and results presented help to understand and develop new strategies for treatments and prevention of biofilm formation. Finally, the methodological approach presented in the present work can be used for several types of bacteria, in different types of surfaces, with different types of topographies and physico-chemical environments that have scientific or technological importance. Bacteria and biofilms generate growing worldwide concern for causing serious problems for human health and for the industry, especially food industry. In this context, the present work contributes to describe the behavior of S. aureus bacteria as a function of surface topography, described with a set of dimensional parameters.